Avaliação do potencial mutagênico, recombinogênico e carcinogênico do Orlistat em células somáticas de Drosophila melanogaster - Orsolin, Priscila Capelari (2011)
CHAPTER 2: Orlistat is the first compound of a new pharmacological class which limits dietary fat absorption by inhibiting gastric and pancreatic lipases. It does not affect the neuronal circuits regulating appetite, and its action consists basically of obstructing digestion of dietary triglycerides. Recent researches suggest that orlistat stops the growth of some tumors because it inhibits the action of fatty acid synthase enzyme, whose activity favors the survival of cancer cells. However, research concerning the long-term use of this drug is unknown, and there are doubts as to possible genotóxico/mutagenic effects from its use. Thus, this study was carried out with the aim of evaluating the mutagenic, recombinogenic and carcinogenic potential of orlistat by means of a test for somatic mutation and recombination test (SMART) and test for epithelial tumor detection (wts), both in Drosophila melanogaster. When analyzed by means of SMART, larvae descending from crosses standard and high bioactivation were chronically treated with three concentrations of orlistat (2.4, 4.8 and 9.6 mg/mL) alone and in combination with DXR (0.125 mg/mL). The results demonstrated recombinogenic effect of orlistat at all concentrations tested in the HB cross and no concentration at the ST cross. In the wts test, conducted with offspring of crosses between virgin females wts/TM3 with males mwh/mwh, larvae were treated with three concentrations of orlistat quoted separately and in combination with mitomycin C (0.1 mM). The results showed that orlistat has no carcinogenic potential, nor reduce tumors induced by mitomycin C. Therefore, in these experimental conditions, orlistat had recombinogenic effects, coupled with the increased presence of cytochrome P450, but was not able to induce or inhibit the occurrence of tumors in D. melanogaster.